A pilot study of differential gene expressions in patients with cough variant asthma and classic bronchial asthma. (3rd June 2022) - Zhou, Guanghong; Zeng, Qingcui; Wei, Wei; Teng, Hong; Liu, Chuntao; Zhou, Zhongwei; Liang, Binmiao; Long, Huaicong
Abstract: Background: Despite extensive exploration of asthma, the mechanism of asthma has not been fully elucidated. Cough variant asthma (CVA) is considered as precursor to classical asthma (CA). Comparative study between CA and CVA may be helpful in further understanding the pathogenesis of asthma. Methods: Peripheral blood mononuclear cells (PBMCs) were isolated from CVA, CA and healthy adults. Each group consisted of five cases. Total RNA was extracted from the PBMCs. Agilent 4 × 44 K human genome oligo microarray was used to detect whole genome expression. Allogeneic clustering, Gene Ontology and KEGG analysis were performed to investigate differentially expressed genes (DEGs). Then, ten candidate genes were screened and verified by real-time PCR. Results: Gene expressions were significantly different among the three groups, with 202 DEGs between the CA and the CVA groups. The Gene Ontology analysis suggested that the DEGs were significantly enriched in 'histone H4-K20 demethylation' and 'antigen processing and presentation of endogenous antigens'. HDC, EGR1, DEFA4, LTF, G0S2, IL4, TFF3, CTSG, FCER1A and CAMP were selected as candidate genes. However, the results of real-time PCR showed that the expression levels of FCER1A, IL4 and HDC in the cough variant asthma group were significantly different from those in the other two groups ( p < 0.05). Conclusions: The pathogenesis of CVA and CA may be related to genes such as FCER1A, HDC and IL4 . Further studies incorporating a larger sample size should be conducted to find more candidate genes and mechanisms.